ANALISIS PENGARUH KOMPETENSI KEPRIBADIAN GURU TERHADAP MOTIVASI BELAJAR PESERTA DIDIK KELAS VI DI SDN 064976 - Sibarani, Herlin Aryani; Salis, Ibnatun; Sirait, Indri Yohana; Nababan, Irma Nurmalita; Gultom, Vidy Vicy; M.Pd., Rahmilawati Ritonga, (Universitas Negeri Medan, 2024)
This literature review examines the importance of teacher personality competencies because of their impact on students' perceptions of learning and educators. Educators who are fair, authoritative, and friendly tend to build a favorable learning environment, thereby increasing students' motivation to learn. The investigation in question concentrates on describing and examining the effect of teacher personality competence on the learning encouragement of students at SDN 064976 Class VI. Qualitative methodology is used by the author, centered on compiling data from diverse literature sources. Primary data acquisition involves library exploration, where related materials are sourced from scientific magazines, books, and essays. These findings reveal an important correlation between teachers' personality competencies and students' motivation to learn. Educators who are characterized by positive attributes such as humor, fairness, and respect for students tend to increase student motivation. Additionally, research identifies that a combination of positive, pleasant attitudes and authoritative behavior among teachers can foster a conducive learning environment, consequently improving students' academic performance. Based on the research results, the authors recommend a higher emphasis on improving teachers' personality competencies in their professional development. Educators must undergo training aimed at perfecting their personalities to become role models for students while fostering a positive and enjoyable learning atmosphere. In addition, educational institutions should introduce initiatives that support the improvement of teachers' personalities to maximize students' learning motivation.Keywords: Influence of personality, teacher personality competence, learning motivation.